60.9k views
2 votes
What is the remainder when (x3 + 1) is divided by (x2 – x + 1)?

A. x+1
B. x
C. 2
D. 0

User Mrsoltys
by
5.9k points

2 Answers

1 vote

Answer: x+1

Explanation:

(x^3+1)/(x^2-x+1)

Factor the expression

= (x+1)(x^2-x+1) / (x^2-x+1)

= x+1

User Derekyy
by
6.1k points
4 votes

Answer:

x+1

Explanation:

x^3 +1 is the sum of cubes

We can factor this into

(a^2 +b^2 ) = (a+b) ( a^2 -ab+b^2)

(x^3+1) = (x+1)(x^2 -1x+1^2)

= (x+1) (x^2 -x+1)

(x^3+1) / (x^2 -1x+1^2)

(x+1) (x^2 -x+1) / (x^2 -x+1)

(x+1)

User Karrtojal
by
6.1k points